2014
DOI: 10.1093/jac/dku082
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus bacteraemia in a UK tertiary referral centre: a 'transoesophageal echocardiogram for all' policy

Abstract: The rate of IE found in SAB is high when TOE is performed first line. There are no clear risk factors to improve yield or the type of echocardiography to be performed. Echocardiography should be performed in all cases and TOE should be considered where it is expected to influence management, as long as local resources allow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…In particular, transoesophageal echocardiography (TEE) is often not performed due to comorbidity, limited acceptance by patients or treating physicians [12], even though other authors showed that performing routinely TEE results in a high incidence of the most feared complication: infective endocarditis [17]. …”
Section: Introductionmentioning
confidence: 99%
“…In particular, transoesophageal echocardiography (TEE) is often not performed due to comorbidity, limited acceptance by patients or treating physicians [12], even though other authors showed that performing routinely TEE results in a high incidence of the most feared complication: infective endocarditis [17]. …”
Section: Introductionmentioning
confidence: 99%
“…Although 5 high-risk criteria had >97% sensitivity and >99% negative predictive value for IE in nosocomial SAB (14), diagnostic properties were less robust when these criteria were applied to a prospective cohort that also included community-acquired and health careassociated SAB (15). Khatib and Sharma (15) found however, the majority did not receive any form of cardiac imaging (14,15), and other studies with higher rates of echocardiography utilization do not support the use of clinical predictors alone to rule out IE (8,12,19).…”
Section: Resultsmentioning
confidence: 99%
“…Identification of IE is crucial because patients require a more complex approach to management, which includes prolonged use of intravenous antibiotic therapy (10,11). The majority of patients with IE do not have clinically evident disease at the time of bacteremia, which makes early diagnosis challenging (4, 8,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Most recently, 13 of 98 SAB patients (16%) were found to have IE in a “mandatory TEE” approach. 15 …”
Section: Results Of Evidence Reviewmentioning
confidence: 99%